A UPLC-Q-TOF/MS and network pharmacology method to explore the mechanism of Anhua fuzhuan tea intervention in nonalcoholic fatty liver disease. Issue 8 (27th March 2023) - Tian, Feng-Ming; Yi, Jian; Tang, Yan; Chen, Bo-Wei; Long, Hong-Ping; Liu, Ying-Fei; Ou-yang, Yin; Zhang, Wen-Jiang; Tang, Rong-Mei; Liu, Bai-Yan
Abstract : The possible mechanism by which the active components of Anhua fuzhuan tea act on FAM in NAFLD lesions was investigated. Abstract : The possible mechanism by which the active components of Anhua fuzhuan tea act on FAM in NAFLD lesions was investigated. 83 components of Anhua fuzhuan tea were analysed by UPLC-Q-TOF/MS. Luteolin-7-rutinoside and other compounds were first discovered in fuzhuan tea. According to the TCMSP database and the Molinspiration website tool to predict and review the literature reports, 78 compounds were identified in fuzhuan tea with possible biological activities. The PharmMapper, Swiss target prediction, and SuperPred databases were used to predict the action targets of biologically active compounds. The GeneCards, CTD, and OMIM databases were mined for NAFLD and FAM genes. Then, a fuzhuan Tea-NAFLD-FAM Venn diagram was constructed. Using the STRING database and CytoHubba program of Cytoscape software, protein interaction analysis was performed, and 16 key genes, including PPARG, were screened. GO function and KEGG enrichment analyses of the screened key genes showed that Anhua fuzhuan tea may regulate FAM in the process of NAFLD through the AMPK signalling pathway, nonalcoholic fatty liver disease pathway, etc . After constructing an active ingredient–key target–pathway map with Cytoscape software, combined with literature reports and BioGPS database analysis, we believe that among the 16 key genes, SREBF1, FASN, ACADM, HMGCR, and FABP1 have potential in the treatment of NAFLD. Animal experiments confirmed the effect of Anhua fuzhuan tea in improving NAFLD and confirmed that this tea can interfere with the gene expression of the above five targets by the AMPK/PPAR pathway, providing support for Anhua fuzhuan tea interfering with FAM in NAFLD lesions.